Bernt Brendemoen: The turkish dialects of Trabzon: their phonology and historical development - Andrić, Marta (Array, 2008)
Rad je prikaz monografije koja obrađuje turske dijalekte područja Trabzona, bliske turskim dijalektima na Balkanu.